Estrutura da comunidade de formigas (Hymenoptera – Formicidae) associada a duas paisagens de caatinga em Milagres –Bahia - Silva, Emerson Mota da (2011)
This study had as objective evaluates the community of ants in two physiognomies of Caatinga (arboreal and shurb) in the country of Milagres, Bahia, Brazil. For such research three trapping methods were used: Pitfall traps, sardine baits and Winkler extractor, this last one was not used in the shrub physiognomy due to litter absence, taking place collections in the dry and wet seasons of the Caatinga. 143 species of ants were found, distributed in 10 subfamilies, and 45 genera; 71 species were found in the physiognomies, 46 exclusive species were found in the arboreal physiognomy and 26 exclusive species in the shrub. The richness of species observed and expected was given by the rarefaction curve (Mao Tau), and for the estimate Jacknife of 1st order. The Mann-Whitney test (p <0,05) showed that are significant difference in the composition of the ant fauna between the physiognomies. However the test of Wilcoxon (p <0,05) didn't show significant difference in the composition of the fauna between dry and wet seasons. The data was also submitted to NMDS and cluster ordination analysis, using the index of Morisita. Both analyses indicated a tendency to cluster the community of ants firstly through collection method.